The horror of incestuous love: trauma at the origin of individual and collective ethics (2014)
The encounter with trauma is linkedto the drama of incestuous love inboth the history of psychoanalysisand the journey of the cure. Thisencounter is developed not onlyas Freud moves from his theory ofsexual seduction, as an event thatlies at the origin of neuroses, to theneed of the fantasm of seductionin the construction of Oedipal reality;but it also reveals its internallogic in a displacement of horror.Experiencing the horror of incestimplies accepting the desire of therealization of incestuous love, devaluatingthe jouissance of this love,and abandoning religious reality toenter the beyond of the fantasm,where there is yet another horror:that of the real. Going through thatother horror is the node of theanalyst’s desire, the beginning ofthe true journey, the journey thatdoes not deprive the human of itsrelation to the Thing, to the enigmaof the origin.